Influence of cyclic variance on the performance of URANS for pulsating flow upstream of an automotive catalyst monolith - Saul, Jonathan; Porters, Sophie; Mat Yamin, Ahmad Kamal; Medina, Humberto; Aleksandrova, Svetlana; Benjamin, Stephen (2015)
CFD predictions using the URANS equations have been compared to phase-averaged and instantaneous PIV pulsating flow fields in a planar diffuser upstream of a catalyst monolith. URANS qualitatively capture the velocity and vorticity fields, in particular the spatial and temporal evolution of the main vortices in the diffuser during the acceleration phase of the cycle. However, they over-predict vortex intensity and hence its residual strength at the beginning of successive pulses. Instantaneous PIV measurements show there is a significant cycle-to-cycle variation in the position and structure of the vortices within the diffuser. This serves to "diffuse" the phase-averaged vortex strength. Alternative simulation techniques such as LES or DNS will be needed if the cyclic variation is to be correctly predicted as this will affect conversion efficiency.